IUmote: A Framework for the Efficient Modelling, Evaluation, and Deployment of Algorithms and Hardware for Underwater Communications - Antonio Sanchez; Angel Perles; Pedro Yuste; Juan V. Capella; Juan Jose Serrano (International Journal of Distributed Sensor Networks)
We present an approach for the modelling and simulating of the modem section of underwater sensor networks. The proposal is based on a specially designed modem architecture and the use of simulation tools and models that represent each of the communication elements: the water medium, physical transducers, electronics, and coding/decoding software. The algorithms can be simulated in the modelling environment; this framework does not require recoding and allows the combination of real and modelled elements. In physical terms, the modem engine provides a decoupled pipelined design of the processing path for the algorithms which allows users to run complex algorithms without requiring a highly demanding specific hardware. The proposal includes a methodology that has allowed us to significantly reduce the effort required in the process, from algorithm development to the effective deployment of the system. As a case study, this paper shows its application and results in the evaluation of a multipath and Doppler-shift correction algorithms.